INTERNATIONAL FINANCE AND THE RISK OF EXCHANGE RATE - Garcia Villegas, Emilio (2010)
Three major aspects are highlighted in international finance), international risks b) international opportunities and c) market imperfections. International risk-financial risks become relevant and insids them the risk of exchange rate that during the last years due to constant fluctuations of currencies like the U.S. dollar, Japanese yen, pound sterling and the euro have impacted economic and financial situation of enterprises. In recent years has been real important to strengthen the senior management in Risk Management. Organizations face a variety of risks and hazards of business are affecting the development, financial and operational, and beyond their operating risks, social, environmental, and ethical issues, which are increasingly global and complex product of the dynamic environment they are embedded. Therefore organizations should have been working to identify and prosecute them manage these risks to acceptable levels, in order to be perceived as opportunities and not threats. Has increased considerably the risk exposure of financial institutions as a result of the significant increase in trading volume and variety of services they provide. The risk is inherent in the financial business, which is why it is essential that financial institutions have adequate systems of internal control. It should establish a formal internal control system, whose main concern is focused on efficient management of risks associated with doing business in direct accordance with strategic business goals. If without this type of system, could jeopardize not only the continuity of the organization, but also the balance and development of the sector in which it operates. The concept of Risk Management consists of a joint process is Risk Assessment and Risk Control. Risk evaluation is a process focused on estimating the impact of risks that could affect the normal performance of an entity collecting the information necessary to enable the organization to make an informed decision about the need for preventive measures.